Designing the architecture of the program system for the estimation and analysis of risks in agricultural integrated production systems - V. I. Loiko; N. V. Efanova (Новые технологии)
The article considers the stages of designing a software package for risk assessment and analysis in agro-industrial integrated production systems, including the development of a modular architecture, the logical structure of the modules included in the software package, physical structure of the software package, software algorithms, and the interface layout.